Development of secretory immunity in breast fed and bottle fed infants. Issue 3 (March 1986) - Stephens, S
Abstract : Samples of saliva and nasal secretions were collected sequentially from 15 breast fed and 15 bottle fed infants on five occasions between 6 days and 9 months of age. Total immunoglobulin concentrations of G, M, and A classes, and class specific antibodies to tetanus toxoid and a pool of commensal strains of Escherichia coli were measured by solid phase radioimmunoassay and expressed per milligram of total protein. There were significant differences between feeding groups, which changed with age. Total IgM and IgA concentrations and IgA antibodies to E. coli were higher in the saliva and nasal secretions of breast fed infants at 6 days. There followed a rapid increase in IgM and IgA concentrations in secretions from all infants, and between 6 weeks and 9 months concentrations were higher in the saliva (but not in the nasal secretions) of the bottle fed group. There were no significant differences between the feeding groups for total IgG, specific G, M, and A antibodies to tetanus toxoid, and G and M antibodies to E. coli. These results suggest that breast feeding enhances secretory immunity in the early neonatal period only. By 6 weeks, local antigens are the main source of stimulation for production of immunoglobulin in the respiratory mucosa and thus may be obscuring any additional stimulation by growth factors in breast milk.